THE BIOLOGICAL OPTIMAL LEVEL OF THE ARAFURA SHRIMP FISHERY - Purwanto Purwanto (Research Center for Fisheries, 2010)
This paper briefly describes the past development of the shrimp fishery in the Arafura Sea, including intensity of illegal fishing, and presents the impact of increasing fishing pressure on the quantity of catch and biomass. The maximum sustainable yield and the optimum fishing effort are estimated.